Challenges to Independence and Overlapping Authorities of Deposit Insurance Institutions in Banking Resolution after Law No. 4 of 2023 on Financial Sector Development and Strengthening - Tuhana Tuhana; Dona Budi Kharisma; Vincentius Farel Oveno Shannon (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2025)
Indonesia's financial system is entering a new phase, particularly its deposit insurance system, with the enactment of Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector. The Deposit Insurance Corporation (LPS), as the deposit insurance and bank resolution authority, has seen its mandate expanded from a paybox model to a risk minimizer, posing new legal challenges. including the potential erosion of the LPS's independence in decision-making due to the requirement for operational budget approval by the Minister of Finance, as well as overlapping authorities with the Bank of Indonesia (BI) and the Financial Services Authority (OJK) during the resolution phase and the placement of funds in troubled banks. This study is a normative legal research conducted using a legal and conceptual approach that examines the involvement of various laws. The legal materials used include primary and secondary legal materials obtained through literature review. Based on the research findings, legal issues faced by the deposit insurance institution were identified, including institutional independence due to the requirement for the Minister of Finance's approval of the LPS's work plan and annual budget, potential overlapping authority with Bank Indonesia's role as the lender of last resort, and the potential weakening of the OJK's position in the bank recovery phase.